A framework for a joint hydro-meteorological-social analysis of drought - Lange, Bettina; Holman, Ian P.; Bloomfield, John P. (Elsevier, 2016)
This article presents an innovative framework for analysing environmental governance challenges by focusing on their Drivers, Responses and Impacts (DRI). It builds on and modifies the widely applied Drivers, Pressures, States, Impacts and Responses (DPSIR) model. It suggests, firstly and most importantly, that the various temporal and spatial scales at which Drivers, Responses and Impacts operate should be included in the DRI conceptual framework. Secondly, the framework focuses on Drivers, Impacts and Responses in order to provide a parsimonious account of a drought system that can be informed by a range of social science, humanities and science data. ‘Pressures’ are therefore considered as a sub-category of ‘Drivers’. ‘States’ are a sub-category of ‘Impacts’. Thirdly, and most fundamentally in order to facilitate cross-disciplinary research of droughts, the DRI framework defines each of its elements, ‘Drivers’, ‘Pressures’, ‘States’, ‘Impacts’ and ‘Responses’ as capable of being shaped by both linked natural and social factors. This is different from existing DPSIR models which often see ‘Responses’ and ‘Impacts’ as located mainly in the social world, while ‘States’ are considered to be states within the natural environment only. The article illustrates this argument through an application of the DRI framework to the 1976 and 2003–6 droughts. The article also starts to address how - in cross-disciplinary research that encompasses physical and social sciences – claims about relationships between Drivers as well as Impacts of and Responses to drought over time can be methodologically justified. While the DRI framework has been inductively developed out of research on droughts we argue that it can be applied to a range of environmental governance challenges.
Keywords: Drought and water scarcity; Drivers; Responses; Impacts; Cross-disciplinary research; Historical analysis